EFFECT OF GARLIC POWDER (ALLIUM SATIVUM LINN) ON REDUCING THE SIGN AND SYMPTOMS OF PULMONARY TUBERCULOSIS - Retno, Retno Twistiandayani; Istiroha; Lajuward, Akhmat Imam (Universitas Nahdlatul Ulama Surabaya, 2024)
Garlic contains substances that function as broad-spectrum antimicrobials that can inhibit the bacteria that cause Tuberculosis (TB). The purpose of this study was to explain the effect of providing garlic powder (Allium Sativum Linn) on reducing the signs and symptoms of pulmonary TB. This study was a quasi-experimental study using a control group pre-posttest design approach. The population of this study were all patients with pulmonary TB at Metatu Health Center, Benjeng, Gresik. The purposive sampling technique was used to recruit respondents and obtained 22 respondents who were divided into treatment groups and control groups. The treatment group received 5gr of garlic powder 3x/day. The instruments used were standard operational procedure and observation sheets for signs and symptoms of pulmonary TB. Data analysis using Paired T-Test test with α < 0.05. The statistical test results obtained p value = 0.000 which means that there was a significant difference in the decrease in signs and symptoms of pulmonary TB before and after the administration of garlic powder. The results of statistical tests in the control group obtained p value = 0.341, which means that there was no significant difference in reducing signs and symptoms of pulmonary TB in the control group. The allicin compound in garlic is able to inhibit the bacteria that cause tuberculosis. The health center is expected to make Standard Operational Procedure related to complementary nursing by giving garlic powder to patients with pulmonary TB.